Conditional Punishment As An Alternative Punishment Of Prevention Crimes In Indonesia - Ratri Novita Erdianti; Sholahuddin Al-Fatih; Wasis Suprayitna (JUSTITIA JURNAL HUKUM, 2021)
Criminal is a tool used in tackling criminal acts. The judge as the part who passes the sentence has a very important role in determining the effectiveness of the punishment that will be imposed on the perpetrator of the criminal act . So in this case the judge should be precise in determining which type of crime is appropriate for the perpetrator, considering that the imposition of a sentence against someone who has committed a criminal act is a very important part of realizing the expected criminal justice system. The application of imprisonment for the short term has many weaknesses. The process of prisonisation becomes a means of crime school for prisoners who have the opportunity to increase the number of existing receivers. Thus an alternative punishment is needed that can be a solution to the weaknesses of imprisonment. Conditional punishment is an alternative punishment that can be imposed by a judge against the perpetrator of a criminal act. The limitation in this research is focused on the use of conditional punishment which is expected to be able to fulfill the desired sentencing objectives and become an effort in criminal policy to tackle crime. This study uses a normative juridical research method that will examine conditional criminality in relation to the theory of the purpose of punishment as well as examine crime as an effort to tackle crime based on the theory of criminal policy.